PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI STIPAS KEUSKUPAN AGUNG KUPANG - Ngongo, Maria Hendritha Lidya; Duka, Gerardus Bernardus (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2020)
The focus of this research is to discover whether leadership style, work motivation, work discipline influence employee performance at the Pastoral Institution of Higher Learning of Kupang Archdiocese. This research is also designed for analyzing which of those three variables that becomes the most dominant factor on employee performance. The results of the descriptive statistics analysis showed that the leadership style was catagorized as good (60,76 %), work motivation as good (59,52 %), work discpline as good (60,77 %), and employee performance was also catagorized as good (60,81 %). The results of t-test showed that partially leadership style (4.117, sig. 0.000 < 0,05), work motivation (4.373, sig. 0.000 < 0,05), work discpline (2.769, sig. 0.006 < 0,05) had a positive and significant effect on the employee performance of Pastoral Institution of Higher Learning, Kupang Archdiocese. The results of F-test indicated that simultaneously the three independent variables: leadership style, work motivation, work discpline (13,777, sig. 0,000 < 0,05) had a positive and significant effect on the employee performance. It is suggested to the management of Pastoral Institution of Higher Learning, Kupang Archdiocese has to make a evaluation on the leadership style and work motivation, evaluation on the work discipline and employee performance, to make a research of the others factor that influence on employee performance. The management of Pastoral Institution of Higher Learning, Kupang Archdiocese is responsibility to improve the leadership style, work motivation, work discipline and employee performance.